2021
DOI: 10.3233/jad-201302
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Advanced Dementia with Late Onset, Young Onset, and Very Young Onset

Abstract: Background: Advanced stages of dementia are characterized by severe cognitive and physical impairment. It has not yet been investigated whether persons with young onset dementia (YOD) and late onset dementia (LOD) differ in advanced disease stages. Objectives: To compare quality of life (QoL) between persons with advanced YOD and LOD; to explore the determinants of QoL; to investigate whether YOD and LOD differ with regard to symptoms and care. Methods: The study was performed in the context of EPYLOGE (IssuEs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The more sedentary services that are developed for older people’s care are not adequate for younger persons with more physical possibilities, as also reported by our respondents. 23 Additionally, the need for dignified care and the fear of being socially isolated emerged. Unavailability of age-appropriate care for people with young-onset dementia and their caregivers is a durable issue: a review showed that findings about its limited availability remain largely unchanged during the past 26 years.…”
Section: Discussionmentioning
confidence: 99%
“…The more sedentary services that are developed for older people’s care are not adequate for younger persons with more physical possibilities, as also reported by our respondents. 23 Additionally, the need for dignified care and the fear of being socially isolated emerged. Unavailability of age-appropriate care for people with young-onset dementia and their caregivers is a durable issue: a review showed that findings about its limited availability remain largely unchanged during the past 26 years.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced dementia was defined as Clinical Dementia Rating [ 17 ] global score 2 or 3. EPYLOGE consisted of two parts: In “part A” a prospective study of palliative care issues in 181 PWAD was conducted, the findings have been reported recently [ 15 ]. In “part B”, which is reported here, a postmortem interview was carried out with the closest relatives of PWAD who had died within the three-year study period of “part A” of EPYLOGE (N = 52) and with relatives of recently deceased PWAD (N = 48) who had additionally been identified through a large Bavarian dementia network (e.g., Munich Alzheimer Society, Alzheimer Society Germany, various long-term care facilities in Bavaria, clinical centers of the German Consortium for Frontotemporal Dementias).…”
Section: Methodsmentioning
confidence: 99%
“…However, palliative care needs remain underinvestigated despite a growing number of studies on people with YOD. The German EPYLOGE-study is the only study on this topic so far [13]. Its cohort consisted of people with advanced YOD and LOD living at home or in long-term care (LTC) facilities.…”
Section: Introductionmentioning
confidence: 99%